Productivity and Economics of Different Double Cropping Systems at Farmer’s Field in Tikamgarh District of Madhya Pradesh - P. K. Tyagi; V. K. Singh (Indian Journal of Extension Education, 2017)
The present study was conducted to assess the productivity and economics of different cropping systems at Farmer’s Field in five blocks of Tikamgarh district of Madhya Pradesh. The pooled data revealed that the total productivity in terms of seed yield (45.0 q/ha) as well as wheat equivalent yield (54.1 q/ha) was recorded the highest in soybean-wheat system. Similarly, the production efficiency (19.3 kg/ha/day) and net monetary return (` 36882/ha) were also recorded the highest in soybean-wheat system. However, net monetary return per day was recorded the maximum in blackgram-coriander system (` 160/ha/day) closely followed by soybean-wheat (` 158/ha/day) system. Soybean-wheat system gave an advantage of a net return of ` 10467, ` 8007 and ` 1310 per hectare over sesame-wheat, blackgram-mustard and blackgram-coriander systems respectively. Similarly, increase in net monetary return from blackgram-coriander over sesame-wheat was ` 9157/ha and over blackgram-mustard was ` 6697/ha. The net return per rupee invested (B:C) was recorded the highest in blackgram-coriander (1.92) and the lowest in sesame-wheat (1.07) system. It was evident from the results that soybean-wheat system exhibited superiority over other cropping systems in Tikamgarh district. Similarly, growing the coriander crop after blackgram was more remunerative than growing mustard crop. Blackgram-coriander system was also profitable over sesame-wheat system.